Influence of hydrocarbon-stapling on membrane interactions of synthetic antimicrobial peptides. Issue 6 (15th March 2018) - Stone, Tracy A.; Cole, Gregory B.; Nguyen, Huong Q.; Sharpe, Simon; Deber, Charles M.
Graphical abstract: Highlights: Designed linear and hydrocarbon-stapled CAPs display similar antimicrobial activity. Hydrocarbon stapling increases membrane interactions, but non-selectively. Polar substitutions restore selectivity for bacterial membranes. Linear and stapled analogs do not function through detergent-like mechanisms. Abstract: Cyclization has been recognized as a valuable technique for increasing the efficacy of small molecule and peptide therapeutics. Here we report the application of a hydrocarbon staple to a rationally-designed cationic antimicrobial peptide (CAP) that acquires increased membrane targeting and interaction vs . its linear counterpart. The previously-described CAP, 6K-F17 (KKKKKK-AAFAAWAAFAA-NH2 ) was used as the backbone for incorporation of an i to i  +  4 helical hydrocarbon staple through olefin ring closing metathesis. Stapled versions of 6K-F17 showed an increase in non-selective membrane interaction, where the staple itself enhances the degree of membrane interaction and rate of cell death while maintaining high potency against bacterial membranes. However, the higher averaged hydrophobicity imparted by the staple also significantly increases toxicity to mammalian cells. This deleterious effect is countered through stepwise reduction of the stapled 6K-F17's backbone hydrophobicity through polar amino acid substitutions. Circular dichroism assessment of secondary structure in various bacterial membrane mimetics reveals that a helical structure may improve – but is not an absolute requirement for – antimicrobial activity of 6K-F17. Further, phosphorus-31 static solid state NMR spectra revealed that both non-toxic stapled and linear peptides bind bacterial membranes in a similar manner that does not involve a detergent-like mechanism of lipid removal. The overall results suggest that the technique of hydrocarbon stapling can be readily applied to membrane-interactive CAPs to modulate how they interact and target biological membranes.